Environmental, social, and governance initiatives pay off : an assessment of the causal relationship between ESG and firm value - Kubiski, Rafael Ukazono (2021)
The relationship between environmental, social, and governance (ESG) initiatives and firm financial performance has been a subject that has long attracted researchers’ and practitioners’ interest. However, studies to date have presented inconclusive results. We argue that the heterogeneity in outcomes may reside in endogeneity problems not adequately addressed in most empirical identification strategies. Thus, this study aims to evaluate the potential causal link between ESG, firm value, and cost of capital. A quasi-natural experiment is employed to overcome this empirical challenge using the enactment of Directive 2014/95/EU as the exogenous shock in difference-in-differences and triple-difference models. This setting is particularly valuable since the regulation made ESG disclosure mandatory to a population of firms throughout the European Union. A propensity score matching procedure is used to establish the treatment and control groups. The final sample consists of 895 firms, with observations from 2009 - 2019. Results show that the regulation was effective in raising the overall level of transparency of corporate ESG practices. More importantly, compared to control firms, treated firms faced a positive incremental impact on their value and a significant reduction in their cost of capital. These findings remain consistent when an alternative sample composed only by European firms is used. This study contributes to the development of the field by providing more credible evidence for causal inference. It also presents practical implications for different audiences, such as governments and policy-makers pursuing policy reforms related to the corporate disclosure of non-financial information, managers looking to incorporate sustainability-related initiatives into their firm’s strategy, and investors interested in the responsible investing movement.